Alteration of m6A RNA Methylation in Heart Failure With Preserved Ejection Fraction - Zhang, Beijian; Xu, Yamei; Cui, Xiaotong; Jiang, Hao; Luo, Wei; Weng, Xinyu; Wang, Yun; Zhao, Yuhong; Sun, Aijun; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Background Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous disease, which pathogenesis is very complex and far from defined. Here, we explored the m6A RNA methylation alteration in patients with HFpEF and mouse model of HFpEF. Methods In this case- control study, peripheral blood mononuclear cells (PMBCs) were separated from peripheral blood samples obtained from 16 HFpEF patients and 24 health control. The change of m6A regulators was detected by quantitative real-time PCR (RT-PCR). A ‘two-hit’ mouse model of HFpEF was induced by a high-fat diet and drinking water with 0.5 g/L of L-NAME. MeRIP-seq was used to map transcriptome-wide m6A in control mice and HFpEF mice, and the gene expression was high-throughput detected by RNA-seq. Results The expression of m6A writers METTL3, METTL4, KIAA1429, m6A eraser FTO, and reader YTHDF2 were up-regulated in HFpEF patients, compared with health control. And the expression of FTO was also elevated in HFpEF mice. A total of 661 m6A peaks was significantly changed by MeRIP-seq. GO analysis revealed that protein folding, ubiquitin-dependent ERAD pathway and positive regulation of RNA polymerase II were three most significantly altered biologic processes in HFpEF. The pathways including proteasome, protein processing in endoplasmic reticulum and PI3K-Akt signaling pathway were significantly changed in HFpEF by KEGG pathway analysis. Conclusions The expression pattern of m6A regulators and m6A landscape are changed in HFpEF. This uncovers a new transcription-independent mechanisms of translation regulation. Therefore, our data suggest that modulation of epitranscriptomic processes such as m6A methylation might be an interesting target for therapeutic interventions.